Theological Interpretation of Scripture as Spiritual Formation - Brandt, Ryan A.; Frederick, John (Biblical Interpretation Series, 2023)
Academic expertise is essential. But have you ever wondered how it itself is spiritually formative? This book, coming from an interdisciplinary assortment of scholars, shows how the exegetical methods of Theological Interpretation of Scripture (TIS) are themselves spiritually formative. This book provides a diverse collection of essays that focus on theological interpretative methods that result in a unique transformational experience not achieved through historical-critical or grammatical-historical approaches alone. Renowned thinkers-such as biblical scholar Ben Witherington III, historical theologian Mark Elliott, and theologian Arthur Sutherland-offer new works that explore how reading theologically can transform theology, cultures, and individuals. These new studies focus on the theological exegesis of such thinkers as Mother Teresa, Thomas Aquinas, Ignatius of Antioch, and Clement of Alexandria. The collection also includes several important and timely pieces that show how theological interpretation leads to moral formation within diverse cultural groups including African American and Latinx communities.